Endosonography - Hawes, Robert H; Fockens, Paul (Saunders Elsevier, 2006)
This book explains everything you need to know to effectively practice endoscopic ultrasound (EUS). The book’s two sections help you learn to manipulate the endoscope and interpret what you see, and offer clear diagnostic guidance on each condition you may come across. • Offers exquisite full-color illustrations with precise representations of Doppler and correlative endoscopy, pathology, and anatomy, to mirror what you see in practice. • Follows a consistent chapter structure for quick and easy reference. • Summarizes and analyzes all the evidence for each procedure in an accompanying literature table to save you time in selecting techniques. • Includes a bonus CD-ROM with video demonstrations of all EUS procedures to help you understand this dynamic modality.
Keywords: Endosonography; radiologie, nukleární medicína a zobrazovací metody; Diagnostic Imaging; diagnostické zobrazování; endosonografie